A new species group from the Daphnia curvirostris species complex (Cladocera: Anomopoda) from the eastern Palaearctic: taxonomy, phylogeny and phylogeography. Issue 3 (17th June 2020) - Kotov, Alexey A; Garibian, Petr G; Bekker, Eugeniya I; Taylor, Derek J; Karabanov, Dmitry P
Abstract: The eastern Palaearctic is a centre of diversity for freshwater cladocerans (Crustacea), but little is known about the evolution and taxonomy of this diversity. Daphnia curvirostris is a Holarctic species complex that has most of its diversity in the eastern Palaearctic. We examined the phylogeography, rates of evolution and taxonomic status for each clade of the D. curvirostris complex using morphological and genetic evidence from four genes. The cybertaxonomical and morphological evidence supported an eastern Palaearctic clade, with at least four species (described here as the Daphnia korovchinskyi sp. nov. group) having diagnostic morphological characters. We also detected convergent morphological characters in the D. curvirostris complex that provided information about species boundaries. Two of the new species ( Daphnia koreana sp. nov. and Daphnia ishidai sp. nov. ) are known from single ponds and are threatened by human activity. Divergence time estimates suggested an ancient origin (12–28 Mya) for the D. korovchinskyi group, but these estimates are complicated by the small number of calibration points.